2016
DOI: 10.1080/00028487.2016.1217928
|View full text |Cite
|
Sign up to set email alerts
|

Age and Stock Analysis Using Otolith Shape in Gags from the Southern Gulf of Mexico

Abstract: On Campeche Bank (CB) in the southern Gulf of Mexico, Gags Mycteroperca microlepis are captured as part of a sequential multispecies fishery. Limited scientific data suggest that the Gag is the third most important commercial species in the region, contributing 21% (total weight) of the overall grouper catch. Neither age nor stock data are currently available for Gags in this region, making it impossible to determine how this species is affected by current fishing practices. Such information is vital for the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…FF, C, RD, R, E and AR for sagitta were calculated and the realtionships between otolith length and shape descriptors were revealed. The usefulness of otolith shape analysis for stock identification and differentiation have already been supported for several fish species (Campana 1999;Tuset et al 2006;Ferguson et al 2011;Zengin et al 2015;Renán et al 2016;Avigliano et al 2017;Teimori and Eslami 2017). Otolith shape can be described in some ways, one of the simplest and useful method is distance measurement.…”
Section: Discussionmentioning
confidence: 99%
“…FF, C, RD, R, E and AR for sagitta were calculated and the realtionships between otolith length and shape descriptors were revealed. The usefulness of otolith shape analysis for stock identification and differentiation have already been supported for several fish species (Campana 1999;Tuset et al 2006;Ferguson et al 2011;Zengin et al 2015;Renán et al 2016;Avigliano et al 2017;Teimori and Eslami 2017). Otolith shape can be described in some ways, one of the simplest and useful method is distance measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the environmental factors which impact some inter- and intra-specific otolith differences (Lombarte, 1992) and the genotypic aspects which specify the otolith morphology, Avigliano et al . (2015) revealed that the method of otolith shape analysis applied for this study was among the successful tools for stock discrimination (Campana & Casselman, 1993; Burke et al ., 2008; Cañás et al ., 2012; Avigliano et al ., 2014) of different species worldwide (Begg & Brown, 2000; Begg et al ., 2001; Brophy & Danilowicz, 2002; Turan, 2004; Galley et al ., 2006; Megalofonou, 2006; Mérigot et al ., 2007; Duarte-Neto et al ., 2008; Renán et al ., 2010; Vieira et al ., 2014; Jemaa et al ., 2015; Libungan et al ., 2015; Jawad et al ., 2017; Mapp et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those relating to other species (Campana & Casselman, 1993; Duarte-Neto et al ., 2008; Renán et al ., 2010; Vieira et al ., 2014; Jemaa et al ., 2015). Elliptic Fourier descriptors (EFD) and principal component analysis (PCA), using SHAPE, can accurately detect small shape variations and evaluate the shape independently of size (Iwata et al ., 1998; Yoshioka et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and have been described as a "flight recorder" of fish (Lecomte-Finiger 1992). They are considered as valuable markers for distinguishing different fish populations (Tuset et al 2003;Petursdottir et al 2006;Zengin et al 2015;Renán et al 2016;Avigliano et al 2019;Mahè et al 2019;Vu and Kartavtsev 2020;Labidi et al 2020;Ghanbarifardi and Zarei 2021;Chen et al 2021). It is critical to determine the phenotypic variations produced by environmental influences in fisheries management and biology.…”
Section: Introductionmentioning
confidence: 99%